Irrigated urban vegetable production in Ghana: Microbiological contamination in farms and markets and associated consumer risk groups - Amoah, Philip; Drechsel, Pay; Abaidoo, Robert C.; Henseler, M. (IWA Publishing, 2007)
Ghana is a typical low-income sub-Saharan African country facing significant sanitation challenges. In Ghana, fresh salads are not part of the normal diet, but have become a common supplement to urban fast food served in streets, canteens and restaurants. In Accra, about 200 000 people consume from such supplements every day. The figure also describes the size of the risk group from contamination, which comprises all income classes including the poor and children. The purpose of this study was to investigate widespread water pollution in urban and peri-urban areas, where 95% of the lettuce consumed in the city is produced. Over 12 months (April 2004–June 2005), lettuce samples from the same production sites in two cities were followed and analyzed along the “farm to fork” pathway for total and faecal coliform (FC) and helminth egg numbers. Questionnaire surveys were conducted among producers, sellers and consumers to quantify lettuce flows to the final risk group. The study identified the farm as the main point of lettuce contamination. Besides the irrigation water, contamination was also attributed to manure application and already contaminated soil. Despite poor sanitary conditions in markets, post-harvest handling and marketing did not further increase the farm-gate contamination levels. To reduce the health risk associated with the consumption of contaminated lettuce; safer farming and irrigation practices are required while the remaining risk could best be addressed where lettuce is prepared for consumption.